Public Relations, the image and the presidencial figure - López Lara, Yolanda (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The study aims to determine the importance of the strategic management of Public Relations in the management of the presidential image in the administration of Lic. Enrique Peña Nieto (December 1, 2012 to November 30, 2018). The element that motivates these aspirations was the collection of memes by Dr. María Teresa Cervantes Loredo, observing that, on social networks, her messages are consumed by virtual communities with true avidity and immediacy with the topics in vogue and in this case it was the voracious critic in the memes of former president Peña Nieto.